Notes on the occurrence of Hypnella pallescens (Hook.) A. Jaeger (Bryophyta, Pilotrichaceae) in Bahia, Brazil. - Vilas Bõas-Bastos, Silvana B.; Bastos, Cid José P. (Acta Botanica Malacitana, 2004)
Notas sobre la ocurrencia del Hypnella pallecens (Hook.) A. Jaeger (Bryophyta, Pilotrichaceae) en la Bahia, Brasil. Key words. Pilotrichaceae, Hypnella pallescens, Phyllodon truncatulus, Atlantic Rain Forest, Brazil, Bahia. Palabras-clave. Pilotrichaceae, Hypnella pallescens, Phyllodon truncatulus, Mata Atlântica, Brasil, Bahia.